Psychological Torture among University Students - Ali Abdullah , Hamdi Barq; Ali, Omar Kazim (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the level of psychological resilience among university students, the statistically significant differences in psychological resilience among university students according to the gender variable (males, females), and the significance of the statistically significant differences in the psychological resilience variable among university students according to the specialization variable (scientific-humanities) The research sample consisted of 380 male and female students. A psychological resilience scale was constructed, consisting of 35 items. The researcher reached the following results: The students in the research sample are characterized by a high level of psychological resilience, and there is no difference in the psychological resilience scale according to the gender variable (males-females). Students majoring in the humanities are characterized by a higher level of psychological resilience than students majoring in the scientific specialization. The students in the research sample were characterized by a high level of psychological resilience and the significance of the statistically significant differences in the psychological resilience variable among university students.